Itar And The Security Exception: Lessons For Developing Indonesian Defensive Satellites - Aris Rahmat Juliannoor; Sefriani (Prophetic Law Review, 2023)
Outer space technological development, pioneered by military superpowers including the USA, China, and Russia gives other countries a variety of technologies which they have chosen to use to strengthen their national defence. “The higher the demand, the more expensive it gets.” A country is free to choose what technology to use, but the producer controls who can use their technology. Policies to limit or control space-technology is most clearly reflected by USA policy, named ITAR (International Trade in Arms Regulation), which enables the USA to choose who is able to avail themselves of space technology. A quasi-arbitrary policy like ITAR has harmed the spirit and the soul of international trade law which empowers the “free trade” market that is happening in today’s world. Policy alike has made the US gripped other countries like Indonesia and made them ‘dependence’ on their sophisticated technology and deprived other state’s sovereignty on their space technology, eventually. This study analysed this unprecedented subject through the lens of International Law, especially International Trade Law, encompassing related laws like GATT (General Agreement on Tariffs and Trades) and related precedents on WTO (World Trade Organization) DSB (Dispute Settlement Body) judicial decisions. The results of analysis through international law, assisted with dependence theory and world-system theory (1) categorize the related policy as a violation of GATT, specifically to Article XXI (b) point (ii) about security exception and (2) for the future of Indonesian outer space development, this country should utilize a security exception clause to release itself from the atrocities of ITAR policy or other similar policies.Keywords: Outer Space, Dependence, International Law, and Policy. Itar Dan Pengecualian Keamanan: Pelajaran Untuk Membangun Satelit Pertahanan Indonesia AbstrakPerkembangan teknologi luar angkasa yang dipelopori oleh negara-negara adidaya militer termasuk Amerika Serikat, China, dan Rusia memberi negara-negara lain berbagai teknologi yang mereka pilih untuk digunakan untuk memperkuat pertahanan nasional mereka. “Semakin tinggi permintaan, semakin mahal harganya.” Suatu negara bebas memilih teknologi apa yang akan digunakan, tetapi produsen mengontrol siapa yang dapat menggunakan teknologi mereka. Kebijakan untuk membatasi atau mengendalikan teknologi luar angkasa paling jelas tercermin dalam kebijakan AS, yang disebut ITAR (International Trade in Arms Regulation), yang memungkinkan AS untuk memilih siapa yang dapat memanfaatkan teknologi luar angkasa. Kebijakan semi-arbitrer seperti ITAR telah mencederai semangat dan jiwa hukum perdagangan internasional yang memberdayakan pasar “perdagangan bebas” yang terjadi di dunia saat ini. Kebijakan serupa telah membuat AS mencengkeram negara lain seperti Indonesia dan membuat mereka 'ketergantungan' pada teknologi canggih mereka dan pada akhirnya mencabut kedaulatan negara lain atas teknologi luar angkasa mereka. Studi ini menganalisis subjek yang belum pernah terjadi sebelumnya ini melalui lensa Hukum Internasional, khususnya Hukum Perdagangan Internasional, yang mencakup undang-undang terkait seperti GATT (Persetujuan Umum tentang Tarif dan Perdagangan) dan preseden terkait pada keputusan yudisial WTO (Organisasi Perdagangan Dunia) DSB (Badan Penyelesaian Sengketa). Hasil analisis melalui hukum internasional dibantu dengan teori ketergantungan dan teori sistem dunia (1) mengkategorikan kebijakan terkait sebagai pelanggaran GATT, khususnya Pasal XXI (b) poin (ii) tentang pengecualian keamanan dan (2) untuk masa depan pembangunan luar angkasa Indonesia, negara ini harus menggunakan klausul pengecualian keamanan untuk melepaskan diri dari kekejaman kebijakan ITAR atau kebijakan serupa lainnya.Kata kunci: Luar Angkasa, Ketergantungan, Hukum Internasional, dan Kebijakan.